Selective Hydrogenation of Polyunsaturated Fatty Acid Methyl Esters over Bifunctional Ligand-Modified Pd/MIL-101(Cr) Catalysts - Khenkhom, Phuwadon; Ritvirulh, Chonlada; Choojun, Kittisak; Preedawichitkun, Yardthip; Chanlek, Narong; Sooknoi, Tawan (My University, 2025)
Highly dispersed palladium nanoparticles (Pd NPs) were incorporated into MIL-101(Cr) frameworks functionalized with bifunctional ligands for the liquid-phase hydrogenation of polyunsaturated fatty acid methyl esters (FAMEs). A series of amino- and carboxylic-acid-containing ligands─ethylenediamine (en), diethylenetriamine (DET), alanine (AN), 4-aminobutyric acid (ABA), 5-aminovaleric acid (AVA), glutamic acid (GA), and adipic acid (AA)─were grafted onto MIL-101(Cr), followed by Pd loading (0.5 wt %). Spectroscopic and structural analyses confirmed ligand coordination to both Cr nodes and Pd species. Catalysts bearing ABA, AVA, and GA exhibited Pd0dispersion (<1 nm), yielding high turnover frequencies (up to ∼15,400  h–1) and >94% selectivity for monounsaturated FAMEs. In contrast, strong Pd–N interactions in en- and DET-grafted materials suppressed Pd0formation, reducing activity. Hot filtration and recyclability tests confirmed high catalyst stability and negligible Pd leaching. The bifunctional ligand architecture effectively tunes Pd speciation and activity, providing a robust platform for selective and reusable hydrogenation catalysts.